The Effect Of Jigsaw Teachnique On Students’ Writing Skill At Eeventh Grade Of SMA Negeri 5 Pematang Siantar - Roma Rejeki Nami Saragih; Christian Neni Purba; Asima Rohana Sinaga (Jurnal Ilmu Pendidikan dan Sosial, 2024)
This research was carried out to find whether or not the effect of Jigsaw technique on students’ writing skill in Analytical Exposition Text at eeventh grade of SMA Negeri 5 Pematang Siantar. The research methodoogy used in this research was a quasi-experimental research. There were two classes taken as the samples of this research, class XI IPS 2 as the experimental class and class XI IPS 4 as the contro class. The mean score in experimental class from pre-test to post-test was 51,66 and 72,22. The mean score in contro class from pre-test to post-test was 54,44 and 61,66. The improvement as the experimental class got in post-test was 20,56 and as the contro class got in post-test was 7,22. The sum of standard deviation in experimental class was 2037,50 and in contro class was 3271,88. The data were colected by administering pre-test and post-test. The research findings showed that there was significant effect by using Jigsaw technique on students’ writing skill. It can be seen from the testing hypothesis, it showed that the t-test value (6,51) was higher than the t-table value (1,98) at leve of significance 5% with degree of freedom (df) was 70. This are by the score of post-test in both classes. The average post-test score in experimental class was 72,22 was higher than the average post-test score in contro class which was 51,66. It can be concluded that there is a significant difference in the writing skill between the students who are taught by using Jigsaw technique on Students’ writing skill in Analytical Exposition Texts and those who are taught without using it.